Building and Sustaining National ICT Education Agencies : Lessons from Armenia (NaCET) - Gaible, Edmond; Shahverdyan, Anush (World Bank, Washington, DC, 2017)
The National Center for Education Technology (NaCET) has for nearly ten years served as the primary support for education technology in Armenian schools. NaCET manages the Armenian Schools Internet Network (ASIN), plus school information management, content development and dissemination, training in information technology, and development and dissemination of education content. NaCET was founded to meet urgent needs for technical capacity and contract management with the Ministry of Education and Science (MoES). In meeting these needs, NaCET has overseen the extension of internet connectivity to more than 99 percent of schools as of 2013. This milestone is accompanied by new pressures - the need to begin the process of upgrading hardware - and by a new opportunity for broader assessment of the role of education technology in schools.